FINGERPRINT ANALYSIS OF BETEL (Piper betle L.) AS RAW MATERIALS OF TRADITIONAL MEDICINE USING FTIR SPECTROSCOPE - Vibrila Berliana Djanas; Fatimawali; Elly Suoth (PHARMACON, 2023)
Betel (Piper betle L.) is a plant that has long been used as a traditional medicine due to its nutritious chemical components in it. These components can be analyzed using the FTIR (Fourier Transform Infra-Red) spectroscopy method which can describe the chemical structure based on the fingerprint spectrum. The purpose of this study was to analyze the fingerprints of betel nut originating from Manado, North Minahasa, Minahasa, and Bitung using the FTIR spectroscopic method. Betel fruit samples were measured in the mid-IR region (4000-650 Cm-1) and obtained 4 FTIR spectra which were relatively the same, then the functional groups were determined for each main peak. The results showed that there were 10 functional groups in 17 absorbance bands for each betel fruit spectrum obtained. Fingerprint analysis of betel fruit with FTIR spectroscopic method can provide an overview of the chemical structure contained in 4 types of betel fruit based on geographically different growing areas.